Ideal Influence and Intellectual Stimulation: Critical Dimensions in Improving MSME Performance in the Digital Transformation Era - Arip Yusup; Hartono Sri; Kristiyana Naning; Hartono Sri; Setiawan Fery (E3S Web of Conferences)
Micro, Small, and Medium Enterprises (MSMEs) are an important pillar of the global and national economy, but they are faced with various major challenges in the era of digital transformation, such as increasingly fierce competition, rapid technological changes, and innovation demands. Effective leadership is a key factor in ensuring the success of MSMEs to survive and thrive in the midst of these challenges. This study aims to examine the influence of two dimensions of transformational leadership, namely Idealized Influence and Intellectual Stimulation, on the performance of MSMEs. The quantitative approach in this study is used by the survey method, where data is collected through questionnaires distributed to MSME owners and managers in various industrial sectors. Data analysis was carried out using linear regression to test the influence of the two dimensions of leadership on MSME performance variables. The results show that Idealized Influence has a significant positive influence on the performance of MSMEs, with leaders who are able to set an example and build trust directly contribute to increasing productivity and organizational performance. In addition, Intellectual Stimulation has been shown to encourage innovation and creativity, which in turn increases the competitiveness of MSMEs in facing digital challenges. The implications of this study are important for MSME leaders to understand the role of transformational leadership in dealing with digital dynamics. Practical recommendations are expected to help MSMEs to be more adaptive, innovative, and competitive in an era that continues to develop.